Innovations in Nuclear Medicine Imaging for Reactive Oxygen Species: Applications and Radiopharmaceuticals - Joo Yeon Park; Sun Mi Park; Tae Sup Lee; Sang Ju Lee; Ji-Young Kim; Seung Jun Oh; Hai-Jeon Yoon; Bom Sahn Kim; Byung Seok Moon (MDPI AG, 2024)
Reactive oxygen species (ROS) are generated during normal cellular energy production and play a critical role in maintaining cellular function. However, excessive ROS can damage cells and tissues, contributing to the development of diseases such as cardiovascular, inflammatory, and neurodegenerative disorders. This review explores the potential of nuclear medicine imaging techniques for detecting ROS and evaluates various radiopharmaceuticals used in these applications. Radiopharmaceuticals, which are drugs labeled with radionuclides, can bind to specific biomarkers, facilitating their identification in vivo using nuclear medicine equipment, i.e., positron emission tomography and single photon emission computed tomography, for diagnostic purposes. This review includes a comprehensive search of PubMed, covering radiopharmaceuticals such as analogs of fluorescent probes and antioxidant vitamin C, and biomarkers targeting mitochondrial complex I or cystine/glutamate transporter.